The mask you live in - Newsom, Jennifer Siebel, 1974-; Congdon, Jessica, 1972-; Representation Project (Organization).; Virgil Films (2016)
The documentary follows boys and young men as they struggle to stay true themselves while negotiating America's limited definition of masculinity.
Originally produced as a motion picture in 2015.
Director of photography, John Behrens ; film editor, Jessica Congdon ; music, Eric Holland.
MPAA rating: Not rated.
DVD; NTSC, region 1; widescreen (16:9); Dolby digital 5.1.
In English; Spanish subtitles.
Closed captioned.
Keywords: Boys -- United States -- Psychology; Young men -- United States -- Psychology; Masculinity -- United States; Masculinity in popular culture -- United States; Men in popular culture -- United States; Misogyny -- United States; Sexism -- United States; Women in popular culture -- United States; Documentary films; Nonfiction films; Video recordings for the hearing impaired